(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
This paper examines the relationship between the volume of transactions and macroeconomic variables on the Tehran Stock Exchange. We are collect data for variables such as liquidity, inflation, exchange rate, the total value of imports and GDP for ten years period of 2009-2019. For analysis of data, have been used regression analytical method and ordinary least squares method (OLS) model. The results indicate that there are relationships between the macroeconomic variables of liquidity, inflation rate, and GDP with the volume of transactions. Therefore, the relationship between the volume of transactions with liquidity and GDP is positive and significant and with inflation is negative.